Characterization of XV7 and XV9 cDNA clones which confer osmotolerance to Eschericia coli - Salie, S (Department of Biological Sciences, 2017)
The sequence similarity between XV7 and the mammalian syntaxin-like protein kinase receptor shows that XV7 may function similar to that of animal protein kinases. The syntaxin-like protein kinase receptor was recently entered into the Genbank (Thoreau, unpublished), therefore not much is known about its characteristics. It does show similarity to a myotonin protein kinase, MtPK (Thoreau, unpublished). The plant receptor-like protein kinases (RLKs) are structurally related to the polypeptide growth factor receptors of animals (Walker, 1994). Although several ABA and stressresponsive gene have been characterised, their physiological role in the initial perception and transduction of stress signals is not well defined Recent reports suggest that characterising phosphorylation/ dephosphorylation responses and investigation of stress-responsive protein kinases may contribute towards identifying the pivotal regulatory steps in plant responses to environmental stress.